2015
DOI: 10.3109/14397595.2015.1069475
|View full text |Cite
|
Sign up to set email alerts
|

Disease activity early in treatment as a predictor of future low disease activity in RA patients treated with iguratimod

Abstract: Iguratimod was effective in RA patients in clinical practice. Our results suggest that 12 weeks may be a sufficient period to judge the medium-term efficacy of iguratimod in patients treated with and without MTX.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…After the primary screening, 104 records were obtained. According to the inclusion and exclusion criteria and the completeness of the literature information, 18 records were excluded from the second screening after reading the full text (GuifengLi, 2014;He et al, 2015;Okamura et al, 2015;Meng et al, 2016a;Lin, 2016;Yoshioka et al, 2016;Zhu et al, 2016;Wang, 2017;Wang et al, 2017; Luo Y. et al, 2018;Wang X. et al, 2018;Huang and Ma, 2018;Luo et al, 2019;Shang et al, 2019;Suto et al, 2019;Gu et al, 2020; ManXie, 2020;Xu et al, 2021), and 86 records [(GuifengLi, 2014;Lü et al, 2008;Tian and Tao, 2017;Qi et al, 2019; Hara et al, 2014; Ishiguro et al, 2013; Li L. et al, 2019;Hu, 2014;Xia et al, 2020;Xia et al, 2016;Lu, 2014;Zhao et al, 2016;Shi et al, 2015;Meng et al, 2015;Bi, 2019;Zhang, 2018;Li et al, 2016;Mo et al, 2018;Duan et al, 2015;Xiong and GengGuanghui, 2020;Shang, 2014;Mo and Ma, 2015;Tian et al, 2020; Xu B. et al, 2015; Xu LM. et al, 2017;Yan and Wang, 2018;Fan et al, 2020;Meng et al, 2016b;Wang L. et al, 2019;…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…After the primary screening, 104 records were obtained. According to the inclusion and exclusion criteria and the completeness of the literature information, 18 records were excluded from the second screening after reading the full text (GuifengLi, 2014;He et al, 2015;Okamura et al, 2015;Meng et al, 2016a;Lin, 2016;Yoshioka et al, 2016;Zhu et al, 2016;Wang, 2017;Wang et al, 2017; Luo Y. et al, 2018;Wang X. et al, 2018;Huang and Ma, 2018;Luo et al, 2019;Shang et al, 2019;Suto et al, 2019;Gu et al, 2020; ManXie, 2020;Xu et al, 2021), and 86 records [(GuifengLi, 2014;Lü et al, 2008;Tian and Tao, 2017;Qi et al, 2019; Hara et al, 2014; Ishiguro et al, 2013; Li L. et al, 2019;Hu, 2014;Xia et al, 2020;Xia et al, 2016;Lu, 2014;Zhao et al, 2016;Shi et al, 2015;Meng et al, 2015;Bi, 2019;Zhang, 2018;Li et al, 2016;Mo et al, 2018;Duan et al, 2015;Xiong and GengGuanghui, 2020;Shang, 2014;Mo and Ma, 2015;Tian et al, 2020; Xu B. et al, 2015; Xu LM. et al, 2017;Yan and Wang, 2018;Fan et al, 2020;Meng et al, 2016b;Wang L. et al, 2019;…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…After carefully reading the full text and comparing the selection criteria, 33 RCTs were screened out and finally included ( Shi et al, 2015 ; Lu 2014 ; Duan et al, 2015 ; Xiong et al, 2020 ; Xu et al, 2015 ; Ding et al, 2019 ; Deng et al, 2017 ; Tian et al, 2020 ; Xie et al, 2018 ; Xu et al, 2017 ; Bi et al, 2019 ; Yan et al, 2018 ; Tian et al, 2017 ; Chen et al, 2018 ; Xiong et al, 2015; Mo et al, 2015 ; Fan et al, 2020 ; Zhao et al, 2018 ; Li et al, 2020 ; Li et al, 2019 ; Meng et al, 2017 ; Li et al, 2016 ; Xia et al, 2020 ; Meng et al, 2015 ; Mo et al, 2018 ; Meng et al, 2016 ; Wang et al, 2019 ; Qi et al, 2019 ; Ju et al, 2020 ; Zhao et al, 2016 ; Hara et al, 2014 ; Ishiguro et al, 2013 ; Xia et al, 2016 ) ( Figure 1 ). The main reason why 12 studies were excluded is that eight studies are not RCTs ( Yoshioka et al, 2016 ; Wang et al, 2017 ; Suto et al, 2019 ; Okamura et al, 2015a , b ; Wang 2017 ; Meng et al, 2016 ; Gu et al, 2020 ), and the other four studies are not comparing IGU + MTX with MTX ( Liu 2016 ; Xu et al, 2017 ; Lu and Liu 2018 ; Zhu 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, MMP-3 is a highly relevant biomarker in the context of RA, although there are no currently available agents that specifically target MMP-3 activity. Several recent studies in patients with RA have reported that baseline elevated MMP-3 is predictive of radiographic progression [31], and that treatment of patients with RA with either methotrexate or iguratimod lowers MMP-3 [31,[70][71][72][73][74][75].…”
Section: Discussionmentioning
confidence: 99%